2013
DOI: 10.1016/j.jacc.2013.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and the Risk of Sudden Cardiac Death

Abstract: Objective To identify the risk of sudden cardiac death (SCD) associated with obstructive sleep apnea (OSA). Background Risk stratification for SCD, a major cause of mortality, is difficult. OSA is linked to cardiovascular disease and arrhythmias, and has been shown to increase the risk of nocturnal SCD. It is unknown if OSA independently increases the risk of SCD. Methods We included 10,701 consecutive adults undergoing their first diagnostic polysomnogram between 7/1987 and 7/2003. During follow-up up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
314
0
21

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 528 publications
(341 citation statements)
references
References 22 publications
6
314
0
21
Order By: Relevance
“…Clinically, nocturnal oxygen desaturation is independently associated with prevalence of cardiovascular diseases,13 correlates well with severity of coronary atherosclerosis using invasive coronary angiography,14 and may be an independent predictor of mortality 15. Previous large‐scale studies found that decreases in nocturnal oxygen saturation16 and lowest (nadir) nocturnal oxygen saturation (minSaO 2 ) <78%,5 but not AHI, were independently associated with an increased risk of incident atrial fibrillation and sudden cardiac death, respectively. In a study of MI patients, we reported that minSaO 2 , but not AHI, was independently associated with impaired endothelial function,7 a marker of cardiovascular risk 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, nocturnal oxygen desaturation is independently associated with prevalence of cardiovascular diseases,13 correlates well with severity of coronary atherosclerosis using invasive coronary angiography,14 and may be an independent predictor of mortality 15. Previous large‐scale studies found that decreases in nocturnal oxygen saturation16 and lowest (nadir) nocturnal oxygen saturation (minSaO 2 ) <78%,5 but not AHI, were independently associated with an increased risk of incident atrial fibrillation and sudden cardiac death, respectively. In a study of MI patients, we reported that minSaO 2 , but not AHI, was independently associated with impaired endothelial function,7 a marker of cardiovascular risk 17…”
Section: Introductionmentioning
confidence: 99%
“…Although seldom recognized by clinicians, the prevalence of OSA in patients hospitalized for myocardial infarction (MI) is >60% using an apnea‐hypopnea index (AHI) ≥5 events/h,2 and >40% for an AHI ≥15 events/h 2, 3. OSA has been reported as an independent risk factor for the development of MI and for sudden cardiac death 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…OSAS is a progressive chronic disease that directly influences quality of life, given that sleep is a brain function that is essential to life and aids in relieving human stress. 1,7,8,[12][13][14] While obesity is one of the major risk factors for developing OSAS, it is the only one that is reversible. According to the World Health Organization (WHO), an individual is considered obese when he or she has an abnormal or excessive energy reserve in the form of fat.…”
Section: Introductionmentioning
confidence: 99%
“…1 Cerebral hypoxic and ischemic injuries are involved in many CNS diseases that can be acute, as promoted by occlusion of large arteries 2 and intrapartum, 3 or chronic, as promoted by sleep apnea 4 and rare vascular conditions like Moyamoya disease. 5 In addition, silent chronic brain infarction, which exhibits no apparent symptoms, is directly associated to increased morbidity and mortality in aged populations.…”
Section: Introductionmentioning
confidence: 99%